Retardation of fatigue crack growth in high strength steel S690 using a modified stop-hole technique. (January 2017) - Razavi, S.M.J.; Ayatollahi, M.R.; Sommitsch, C.; Moser, C.
Highlights: Double stop drill-hole (SDH) method was proposed with higher fatigue life improvement. The new method was studied experimentally and numerically for a SENT specimen. The fatigue crack initiation and crack growth lives were determined. Very good agreement was found between the experimental and numerical results. Fatigue life of double SDH was significantly higher than that of single SDH. Abstract: The purpose of this paper is to study the effects of a new stop-hole technique on the subsequent delay in fatigue crack propagation. Single edge notch tension specimens of S690 steel alloy are used to perform the fatigue crack initiation/growth tests under cyclic stress loading. A parametric study is conducted on different geometrical parameters of double stop-hole. The experimental procedure is simulated using finite element analysis and fatigue life models. The experiments including fatigue crack initiation/growth measurements and microscopic examinations beside the numerical results show that the fatigue life extension caused by the double stop-hole method is significantly more than that of the conventional single stop-hole method. The lower stress level around the double stop-hole plays an important role in increasing the fatigue initiation life from the stop-hole edge.